DESIGNING LEARNING MATERIALS FOR TEACHING STUDENTS OF ENGLISH VILLAGE OF SUNGAI DERAS VILLAGE - Dian Islamiati; Aunur rahman; Maliqul Hafis (IKIP PGRI Pontianak, 2023)
The purpose of this research is to describe the learning need analysis and validity level of supplementary learning module to teach students of English village in Sungai Deras. This research uses Research and Development with ADDIE model, which consists of 5 main stage, namely analysis, design, development, implementation, and evaluation. The subject of this research were student at English Village in Sungai Deras. The technique of data collection is indirect communication techniques. The data collection tools applied in this research were validation expert sheet and questionnaires. Validation expert sheet was used to get the data validity, meanwhile questionnaires was used to get data the practicality of learning need analysis. The result of this research based on the data collected showed that the level of validation of supplementary learning module from the material, language, presentation, and graphic aspects is white an average value of 76.04% including feasibility criteria. This mean that using supplementary learning module to teach students of English Village in Sungai Deras village classified as feasibility and practical to use. Meanwhile, need analysis of the Sungai Deras English village’s needs based on the results of the data need analysis questionnaire, there are 2 themes namely, the needs of the Sungai Deras English village and the planning of Sungai Deras English village.